An overview of the application of property market modelling in Malaysia - Norhaya Kamarudin; Suriatini Ismail; Hishamuddin Mohd Ali; Ibrahim Sipan; Fauziah Raji
This paper examines the application of property market models in Malaysia. The aim is to determine the relevance, success and trend of models in explaining problems of the property market. The theoretical underpinning of the property market situation. Through the analysis on research applying property market models, this research evaluates the application of property market modelling in Malaysia. The SWOT analysis enables the identification of the problems and the advantages of applying models for understanding property market behaviour. analysis of the strength, weakness and issues suggests that the main strength lies on the ability of the models to provide an objective explanation to property market problems and its ability to link to other technological innovations, which are useful for resolving real estate problems. The Malaysian experience in this field is relatively new but nevertheless it has significant contribution towards the application of models in real estate research.